2002
DOI: 10.1016/s0092-8674(02)01134-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Small Molecules by Nascent RNA

Abstract: Thiamin and riboflavin are precursors of essential coenzymes-thiamin pyrophosphate (TPP) and flavin mononucleotide (FMN)/flavin adenine dinucleotide (FAD), respectively. In Bacillus spp, genes responsible for thiamin and riboflavin biosynthesis are organized in tightly controllable operons. Here, we demonstrate that the feedback regulation of riboflavin and thiamin genes relies on a novel transcription attenuation mechanism. A unique feature of this mechanism is the formation of specific complexes between a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
229
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 620 publications
(234 citation statements)
references
References 26 publications
5
229
0
Order By: Relevance
“…Binding of uncharged tRNA and small molecules such as thiamine pyrophosphate, flavin mononucleotide, SAM, and guanine has been shown to control premature transcription termination (12,(15)(16)(17)(18)(19)(20); it has been suggested that riboflavin and thiamine biosynthesis genes in Gram-negative bacteria are instead regulated at the level of translation initiation (17)(18)(19). In this study, we find that the B. subtilis lysC gene is regulated by direct interaction of lysine, the final product of the lysine biosynthesis pathway, with the lysC leader RNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of uncharged tRNA and small molecules such as thiamine pyrophosphate, flavin mononucleotide, SAM, and guanine has been shown to control premature transcription termination (12,(15)(16)(17)(18)(19)(20); it has been suggested that riboflavin and thiamine biosynthesis genes in Gram-negative bacteria are instead regulated at the level of translation initiation (17)(18)(19). In this study, we find that the B. subtilis lysC gene is regulated by direct interaction of lysine, the final product of the lysine biosynthesis pathway, with the lysC leader RNA.…”
Section: Discussionmentioning
confidence: 99%
“…The S box regulatory system also involves transcription termination, but in this case the regulated genes respond in concert to a single effector, Sadenosylmethionine (SAM), which binds to the leader RNA and promotes a structural rearrangement that stabilizes the terminator helix (14)(15)(16). Similarly, thiamine pyrophosphate, flavin mononucleotide, and guanine regulate thiamine, riboflavin, and purine biosynthesis genes, respectively, via direct interaction with the leader RNA (17)(18)(19)(20). There are also many systems in which modulation of the leader RNA structure is determined by binding of a regulatory protein that responds to the availability of the effector molecule.…”
mentioning
confidence: 99%
“…1). Recently, three regulons responsible for vitamin biosynthesis have been shown to use flavinmononucleotide, thiamin pyrophosphate (TPP), and adenosyl-cobalamin to directly bind their cognate leader RNAs, changing their structures and functions (2)(3)(4)(5). Such leader RNA aptamers were called riboswitches to reflect their unique ability to switch between two conformations in response to binding of a small molecule without the help of proteins (3,5,6).…”
mentioning
confidence: 99%
“…Recently, three regulons responsible for vitamin biosynthesis have been shown to use flavinmononucleotide, thiamin pyrophosphate (TPP), and adenosyl-cobalamin to directly bind their cognate leader RNAs, changing their structures and functions (2)(3)(4)(5). Such leader RNA aptamers were called riboswitches to reflect their unique ability to switch between two conformations in response to binding of a small molecule without the help of proteins (3,5,6). The evolutionarily conserved sequences encoding vitamin-sensing riboswitches have been found in the genomes of many Gram-positive and Gram-negative bacteria (7)(8)(9)(10), and also in some archaea (10), fungi, and plant species (A.S.M.…”
mentioning
confidence: 99%
See 1 more Smart Citation